OPRM1 gene variants modulate amphetamine-induced euphoria in humans - Dlugos, Andrea M. (2010)
The μ-opioid receptor is involved in the rewarding effects of not only opioids like morphine but also psychostimulants like amphetamine. This study aimed to investigate associations between subjective response to amphetamine and genetic polymorphisms and haplotypes in the μ-opioid receptor including the exonic variant rs1799971 (Asp40Asn). 162 Caucasian volunteers participated in three sessions receiving either placebo or d-amphetamine (10 and 20 mg). Associations between levels of self-reported Euphoria, Energy and Stimulation (ARCI-49) after d-amphetamine ingestion and polymorphisms in OPRM1 were investigated. The intronic SNPs rs510769 and rs2281617 were associated with significantly higher ratings of Euphoria, Energy and Stimulation after 10 mg amphetamine. Feelings of Euphoria, Energy and Stimulation were also found to be associated with a 2-SNP haplotype formed with rs1799971 and rs510769 and a 3-SNP haplotype formed with rs1918760, rs2281617 and rs1998220. These results support the hypothesis that genetic variability in the μ-opioid receptor gene influences the subjective effects of amphetamine and may suggest new strategies for prevention and treatment of psychostimulant abuse.